Severe Fever with Thrombocytopenia Syndrome Virus Antigen Detection Using Monoclonal Antibodies to the Nucleocapsid Protein. - Aiko Fukuma; Shuetsu Fukushi; Tomoki Yoshikawa; Hideki Tani; Satoshi Taniguchi; Takeshi Kurosu; Kazutaka Egawa; Yuto Suda; Harpal Singh; Taro Nomachi; Mutsuyo Gokuden; Katsuyuki Ando; et al. (Public Library of Science (PLoS), 2016)
Severe fever with thrombocytopenia syndrome (SFTS) is a tick-borne infectious disease with a high case fatality rate, and is caused by the SFTS virus (SFTSV). SFTS is endemic to China, South Korea, and Japan. The viral RNA level in sera of patients with SFTS is known to be strongly associated with outcomes. Virological SFTS diagnosis with high sensitivity and specificity are required in disease endemic areas.We generated novel monoclonal antibodies (MAbs) against the SFTSV nucleocapsid (N) protein and developed a sandwich antigen (Ag)-capture enzyme-linked immunosorbent assay (ELISA) for the detection of N protein of SFTSV using MAb and polyclonal antibody as capture and detection antibodies, respectively. The Ag-capture system was capable of detecting at least 350-1220 TCID50/100 μl/well from the culture supernatants of various SFTSV strains. The efficacy of the Ag-capture ELISA in SFTS diagnosis was evaluated using serum samples collected from patients suspected of having SFTS in Japan. All 24 serum samples (100%) containing high copy numbers of viral RNA (>105 copies/ml) showed a positive reaction in the Ag-capture ELISA, whereas 12 out of 15 serum samples (80%) containing low copy numbers of viral RNA (<105 copies/ml) showed a negative reaction in the Ag-capture ELISA. Among these Ag-capture ELISA-negative 12 samples, 9 (75%) were positive for IgG antibodies against SFTSV.The newly developed Ag-capture ELISA is useful for SFTS diagnosis in acute phase patients with high levels of viremia.